1970
DOI: 10.1079/bjn19700080
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding procedure on closure of the oesophageal groove in young sheep

Abstract: 1. Barium sulphate suspensions were given to young sheep by mouth or by injection via an oesophageal catheter. Closure of the oesophageal groove was assessed by observing radiographically whether the suspension passed to the ruminoreticulum or to the abomasum.2. Complete closure of the groove took place in lambs that were trained to drink small meals from a trough after being weaned from their dams, a finding similar to that for lambs weaned on to a teat-bottle.3. When barium was injected into the oesophagus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
4

Year Published

1988
1988
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 6 publications
2
36
0
4
Order By: Relevance
“…From sugars such as lactose, volatile free fatty acids (VFFA) are produced (16). It has been shown that the production of these VFFA's stimulates the growth of ruminal papillae, the development of rumen movements, and ruminal growth (13,17). From our observations it can be concluded that the onset of these functions occurs even without the availability of any roughage.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…From sugars such as lactose, volatile free fatty acids (VFFA) are produced (16). It has been shown that the production of these VFFA's stimulates the growth of ruminal papillae, the development of rumen movements, and ruminal growth (13,17). From our observations it can be concluded that the onset of these functions occurs even without the availability of any roughage.…”
Section: Discussionsupporting
confidence: 54%
“…The reticular groove reflex has been studied intensively in the past (7,12,13,14,16,20,21). Most of these studies were done in lambs, and in almost all cases the animals were allowed to suck a rubber nipple attached to a bottle or a bucket.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there are reports that ensalivation during mastication effectively brings soluble diet components into solution in cattle (Bailey 1961), and that the reticular groove can retain its ability to close completely in conditioned domestic ruminants (Orskov et al 1970;Ruckebusch and Kay 1971;Dobarganes Garcia et al 2005). In combination, these observations led to the hypothesis that nutrients dissolved in saliva bypass the rumen via the reticular groove even in adult individuals -especially in browsing ruminants (Hofmann 1989).…”
Section: Introductionmentioning
confidence: 99%